Спектрально-просторове узгодження параметрів приймальної системи лідару - Харченко, С. О. (ХНУРЕ, 2024)
The paper is presents the analysis of the reception system resonant lidar. Basic formulas for a passband of the frequency filter in view of parameters of the reception telescope are considered. Recommendations concerning the sizes of the reception mirror for various operating conditions lidar are presented.
Keywords: приймальна система лідару; спектрально-просторове узгодження параметрів